Why do some studies find that CPR fraction is not a predictor of survival?. (July 2016) - Wik, Lars; Olsen, Jan-Aage; Persse, David; Sterz, Fritz; Lozano, Michael; Brouwer, Marc A.; Westfall, Mark; Souders, Chris M.; Travis, David T.; Herken, Ulrich R.; Lerner, E. Brooke
Abstract: Introduction: An 80% chest compression fraction (CCF) during resuscitation is recommended. However, heterogeneous results in CCF studies were found during the 2015 Consensus on Science (CoS), which may be because chest compressions are stopped for a wide variety of reasons including providing lifesaving care, provider distraction, fatigue, confusion, and inability to perform lifesaving skills efficiently. Objective: The effect of confounding variables on CCF to predict cardiac arrest survival. Methods: A secondary analysis of emergency medical services (EMS) treated out-of-hospital cardiac arrest (OHCA) patients who received manual compressions. CCF (percent of time patients received compressions) was determined from electronic defibrillator files. Two Sample Wilcoxon Rank Sum or regression determined a statistical association between CCF and age, gender, bystander CPR, public location, witnessed arrest, shockable rhythm, resuscitation duration, study site, and number of shocks. Univariate and multivariate logistic regressions were used to determine CCF effect on survival. Results: Of 2132 patients with manual compressions 1997 had complete data. Shockable rhythm ( p  < 0.001), public location ( p  < 0.004), treatment duration ( p  < 0.001), and number of shocks ( p  < 0.001) were associated with lower CCF. Univariate logistic regression found that CCF was inversely associated with survival (OR 0.07; 95% CI 0.01–0.36). Multivariate regression controlling for factors associated with survival and/or CCF found that increasing CCF was associated with survival (OR 6.34; 95% CI 1.02–39.5). Conclusion: CCF cannot be looked at in isolation as a predictor of survival, but in the context of other resuscitation activities. When controlling for the effects of other resuscitation activities, a higher CCF is predictive of survival. This may explain the heterogeneity of findings during the CoS review.